Innate Immune Sensing by Cells of the Adaptive Immune System - Stögerer, Tanja; Stäger, Simona (Frontiers in Immunology, 2020)
Sensing of microbes or of danger signals has mainly been attributed to myeloid innate immune cells. However, T and B cells also express functional pattern recognition receptors (PRRs). In these cells, PRRs mediate signalling cascades that result in different functions depending on the cell’s activation and/or differentiation status, on the environment, and on the ligand/agonist. Some of these functions are beneficial for the host; however, some are detrimental and are exploited by pathogens to establish persistent infections. In this review, we summarize the available literature on innate immune sensing by cells of the adaptive immune system and discuss possible implications for chronic infections.